Analysis of Mathematic Critical Thinking Abilities of 4th Class Primary School Students on Fraction Material as well as Gender Differences - Aulia, Syafira Nur Azmi; Sutarni, Sri (Prima: Jurnal Pendidikan Matematika, 2024)
The purpose of this study was to assess the mathematical critical thinking abilities of fourth-grade elementary school students. The research was conducted on a sample of students from class IVB at SD Negeri 1 Gatak, who were given a written test consisting of 4 questions on equivalent fractions to evaluate their mathematical critical thinking abilities. The study was titled "Analysis of the Mathematical Critical Thinking Ability of Grade IV Elementary School Students on Equivalent Fraction Material in Terms of Gender Differences". The results of the research indicated that female students outperformed male students in critical mathematical thinking. This conclusion was supported by recorded interviews with several research subjects during the preliminary study, where it was found that many of the subjects struggled to comprehend the steps required to solve mathematical problems based on critical thinking skills. Furthermore, the teachers had not provided examples of questions geared towards critical thinking skills, nor had they implemented teaching concepts based on mathematical critical thinking skills.